"Cuadernos de medicina familiar". Aportes para un enfoque integral de salud - Abelardo E. Rahal (Revista de Salud Pública, 2014)
Autores: JUAN C.ESTARIO; MARÍA B. CIUFFOLINI; MARISA DIDONI; HUMBERTO JURE